2018
DOI: 10.1080/07420528.2018.1463236
|View full text |Cite
|
Sign up to set email alerts
|

Associations between chronotype, sleep disturbances and seasonality with fatigue and inflammatory bowel disease symptoms

Abstract: Growing number of studies suggests link between circadian rhythms and inflammatory bowel diseases (IBD) manifestation. We hypothesize that: 1) IBD are associated with increased eveningness and sleep disturbances; 2) eveningness and sleep disturbances are related to more severe IBD symptoms. In total, 129 participants were enrolled to this study, divided into three groups: 34 Crohn's disease (CD) patients, 38 ulcerative colitis (UC) patients and 57 healthy controls (HC) group. They all fulfilled a questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 42 publications
0
30
0
1
Order By: Relevance
“…Previous studies on the association between chronotype and fatigue in other populations showed mixed results. One study showed that morning type individuals with irritable bowel symptoms reported less fatigue compared with evening types while this association was absent in healthy controls (Chrobak et al, 2018). Another study showed increased levels of chronic work-related fatigue in evening type student-workers compared with morning and intermediate types (Martin et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies on the association between chronotype and fatigue in other populations showed mixed results. One study showed that morning type individuals with irritable bowel symptoms reported less fatigue compared with evening types while this association was absent in healthy controls (Chrobak et al, 2018). Another study showed increased levels of chronic work-related fatigue in evening type student-workers compared with morning and intermediate types (Martin et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The reason to study the associations between chronotype and cancer-related fatigue and sleep quality and cancer-related fatigue is three-fold. First, studies in other populations showed associations between eveningness and fatigue (Soreca et al, 2009; Martin et al, 2012; Chrobak et al, 2018; Caruso et al, 2020) suggesting that this association might also be present in other populations. Second, it provides information on the potential working mechanism of morning light therapy as a treatment for fatigue after cancer (Ancoli-Israel et al, 2012; Redd et al, 2014; Johnson et al, 2017).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Population-based sleep quality studies estimate that 32% of adults report poor sleep. Sleep deficiency is an even more common issue among patients with IBD with numerous authors including Graff et al suggesting rates of problematic sleep in individuals with both active and inactive IBD to be greater than 50% [5,32,84,[93][94][95][96].…”
Section: Sleep Disturbance and Fatiguementioning
confidence: 99%
“…While there are data to support that IBD patients have circadian rhythm disruption, additional studies are needed. Chronotype may be an overlooked factor contributing to IBD, specifically that an evening chronotype may be associated with poorer outcomes and more aggressive disease course [18,19,126]. However, it is important to note that the relative contribution of chronotype compared to the involvement of other factors such as circadian rhythms, sleep duration or other sleep factors have not been well examined.…”
Section: (33) Peptic Ulcermentioning
confidence: 99%